Pengaruh inlet hub angle terhadap daya turbin propeller pada aliran horisontal - H. Bisri (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
Now ULH-related research has become a trend among researchers in hydroelectric power. One form of ULH can be water in pipe. Meanwhile, utilization of horizontal channels as power plants is still low, because the yields obtained are not large enough. Utilization of ULH horizontal flow can be an interesting topic for renewable energy at pico scale, where the reaction turbine that is suitable in this case is propeller turbine. The advantages of propeller turbines are practical, high efficiency, simple, and low production costs. Propeller rotors used in this study had a diameter of 83 mm and a blade inclination of 25°. This study uses addition of a static bulb body to increase the speed of fluid flow, ratio of static bulb used in this study is 0.6. Discharge used is varied from 7 l/s, 9 l/s, 11 l/s, and 13 l/s. This study aims to determine the effect of inlet hub angle blade of turbine performance on horizontal flow in pipe. The highest results on use of the largest discharge are 33° inlet hub angle which produces 17.2 watts at 1283 RPM shaft rotation, and the coefficient of performance (CP) obtained reaches 54%. However increasing the value of the inlet angle of blade hub does not linearly increase the value of mechanical power. The blade with an inlet angle of 44° has the smallest performance, the mechanical power generated is only 13.9 watts at 1045 RPM.